Comparative Effects of Iron Chelators on the Transfusion-Dependent Beta-Thalassemia Patients - Alam, Muhammad Mahbub ul; Alauddin, M; Rahman, M Jollilur; Akhter, Rawshan; Das, Chinmoy Kanti (TAJ: Journal of Teachers Association, 2018)
This prospective study assessed the quality of life of patients with transfusion-dependent beta-thalassemia receiving three different iron chelation treatments. Patients enrolled were receiving one of the following chelation therapies: Group-I: deferoxamine (n=21), Group-II: deferasirox (n=75) and Group-III: deferoxamine in combination with deferiprone (n=39). The three groups were compared in terms of their quality of life, satisfaction and adherence to treatment, control of their health, and self-esteem through the completion of five questionnaires. A higher percentage of patients receiving deferoxamine felt that their treatment negatively influenced their body and skin appearance and limited their ability to work, attend school, and perform daily tasks (P=.0.0066). The adherence to treatment rate and self-esteem were the lowest in the deferoxamine group (P<0.05). The deferoxamine group also had the lowest physical component summary score in the SF-36 questionnaire (P=0.014). This study suggests that the quality of life of beta-thalassemia patients receiving chelation therapy is dependent on the type of iron chelation treatment they receive. The study provides insight into important factors associated with the quality of life of these patients, which are essential for developing a more suitable clinical support team and counseling in order to maximize the treatment benefits for these patients in daily clinical practice. TAJ 2013; 26: 14-19